2017
DOI: 10.1007/s40430-017-0709-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of monotube magnetorheological damper under shear mode

Abstract: a comparative study of the optimised and non-optimised results was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Ferdauss et al [13] considered different configurations of MR damper in the optimisation process to identify the optimal design variable to achieve better performance using FEA-based optimisation. Gurubasavaraju et al [14] carried out design optimisation of monotube MR damper using FE-based response surface optimisation to predict the optimal values of design variable which influences the performance of MR damper. Hu et al [15] carried out design optimisation by considering various piston configurations of MR damper to investigate their influence on the damping.…”
Section: Introductionmentioning
confidence: 99%
“…Ferdauss et al [13] considered different configurations of MR damper in the optimisation process to identify the optimal design variable to achieve better performance using FEA-based optimisation. Gurubasavaraju et al [14] carried out design optimisation of monotube MR damper using FE-based response surface optimisation to predict the optimal values of design variable which influences the performance of MR damper. Hu et al [15] carried out design optimisation by considering various piston configurations of MR damper to investigate their influence on the damping.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that MRF with optimum mean particle size of 2.9 microns and 74.48% particle loading yielded maximum damping force of 566.9 N for minimum off-state viscosity of 0.354 Pa s at magnetic field strength of 96.9 kA/m. (17) Damping force = 340−3.5 × particle size − 12.5 × particle loading + 0.16 × magnetic field strength + 0.1898 × particle loading × particle loading − 0.00419 × magnetic field strength × magnetic field strength − 0.084 × particle size × particle loading − 0.1025 × particle size × magnetic field strength + 0.0262 × particle loading × magnetic field strength…”
Section: Determination Of Optimal Particle Loading and Size Using Mulmentioning
confidence: 99%
“…Hu et al [16] studied the response of a double-coil MR damper while considering various pistons with different configurations and obtained an optimized design based on length of electromagnetic path resistance and damper core radius. Gurubasavaraju et al [17] performed optimization of geometry of a shear mode monotube magnetorheological damper to maximize magnetic flux density in the shear gap by considering shear gap, number of turns of the electromagnetic circuit, flange length and current as design variables for optimization. Shivaram and Gangadharan [18] reported that magnetic field strength and volume fraction of the iron particles have a major influence on the damping force and that the selection of damping materials should be based on application as there is a significant dependence of frequency on the damping force.…”
Section: Introductionmentioning
confidence: 99%
“…2a, b, respectively. The shaft of 10-mm diameter is made of SS 304 stainless steel to (7) yp = −0.8239 + 0.3668 × H − 7 × 10 −4 × H 2 [20]. The magnetic field distribution in the MR brake is shown in Fig.…”
Section: Magnetostatic Analysis Of Mr Brakementioning
confidence: 99%